Protection of Malaysia Small Farmers Under the Plant Variety Law: an Appraisal - Murshamshul Kamariah, M.; Zuhairah Ariff, A.G. (2016)
Plant genetic resources (PGR) is one the most important genetic resources in the agricultural field. PGR play a vital role towards the betterment of global nutrition and health. This article discusses Regarding the appraisal of Protection of Malaysia Small Famers Under the Plant Variety Law. The Revolution, Farmers Right, the Issues, and observation becomes an important discussion of the results and discussion of article.